Impact of SNR, masker type and noise reduction processing on sentence recognition performance and listening effort as indicated by the pupil dilation response - Ohlenforst, Barbara; Wendt, Dorothea; Kramer, Sophia E.; Naylor, Graham; Zekveld, Adriana A.; Lunner, Thomas (Elsevier, 2018)
Recent studies have shown that activating the noise reduction scheme in hearing aids results in a smaller peak pupil dilation (PPD), indicating reduced listening effort, at 50% and 95% correct sentence recognition with a 4-talker masker. The objective of this study was to measure the effect of the noise reduction scheme (on or off) on PPD and sentence recognition across a wide range of signal-to-noise ratios (SNRs) from +16 dB to −12 dB and two masker types (4-talker and stationary noise). Relatively low PPDs were observed at very low (−12 dB) and very high (+16 dB to +8 dB) SNRs presumably due to ‘giving up’ and ‘easy listening’, respectively. The maximum PPD was observed with SNRs at approximately 50% correct sentence recognition. Sentence recognition with both masker types was significantly improved by the noise reduction scheme, which corresponds to the shift in performance from SNR function at approximately 5 dB toward a lower SNR. This intelligibility effect was accompanied by a corresponding effect on the PPD, shifting the peak by approximately 4 dB toward a lower SNR. In addition, with the 4-talker masker, when the noise reduction scheme was active, the PPD was smaller overall than that when the scheme was inactive. We conclude that with the 4-talker masker, noise reduction scheme processing provides a listening effort benefit in addition to any effect associated with improved intelligibility. Thus, the effect of the noise reduction scheme on listening effort incorporates more than can be explained by intelligibility alone, emphasizing the potential importance of measuring listening effort in addition to traditional speech reception measures.